Do we understand voiding dysfunction in women? Current understanding and future perspectives: ICI‐RS 2017. (31st July 2018) - Panicker, Jalesh N.; Anding, Ralf; Arlandis, Salvador; Blok, Bertil; Dorrepaal, Caroline; Harding, Chris; Marcelissen, Tom; Rademakers, Kevin; Abrams, Paul; Apostolidis, Apostolos
Abstract : Aims: Urinary retention in women is poorly understood, compared to the equivalent condition in men, and was the subject of a dedicated session organized at the International Consultation on Incontinence Research Society (ICI‐RS) in Bristol, United Kingdom, 2017. Methods: The current understanding of the pathophysiological correlates of idiopathic voiding dysfunction in women, the role of urodynamics, neurophysiology, and non‐invasive tests in characterizing functional bladder outlet obstruction due to a non‐relaxing urethral sphincter, and poorly defined diagnosis of detrusor underactivity were reviewed. Results: Putative factors underlying the pathogenesis of urinary retention following urinary tract infections were discussed. Further research is required to explore the association between bladder wall inflammation and alterations in detrusor contractile functions. The complex interrelationship between urinary retention and psychological co‐morbidities and sexual trauma were explored, and the overlap between these and psychological co‐morbidities and functional neurological problems with functional urological problems were recognized. Understanding the mechanism of action of sacral neuromodulation, often a successful treatment for urinary retention, would provide insight into the underlying factors that may be responsible for urinary retention. Specifically, there is a need to understand the role of the endogenous enkephalinergic system in the pathogenesis of urinary retention and to identify predictors of successful treatment with sacral neuromodulation. Based on current understanding and potential directions of research in the future, an algorithm for the evaluation of women with voiding dysfunction was proposed. Conclusions: In the future, recommendations for research should lead to a better understanding of urinary retention in women and its treatment.